Pengaruh Media Video Senam Hipertensi terhadap Pengetahuan pada Lansia di Posyandu Lestari - Farlina Nur Islami; Emelia Tonapa; Desie Rahmawati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Hypertension is a global health issue that carries a risk of triggering fatal complications such as stroke and heart failure; older adults are particularly susceptible to it. In Indonesia, there are 63,309,620 people suffering from hypertension at the Lestari Community Health Centre, there are 1,143 eldery with hypertension. This vulnerability is generally triggered by the natural ageing process, which is often exacerbated by a lack of physical activity. The tendency of older adults to maintain a sedentary lifestyle is heavily influenced by their limited education and knowledge regarding the importance of hypertension exercises as a means of management. The elderly’s knowledge of performing hypertension exercises remains limited due to a lack of regular exercise habits. Therefore, innovative educational methods, such as hypertension exercise videos, are required to enhance the elderly’s knowledge in optimally controlling blood pressure. The aim of this study was to determine the effect of a video-based exercise programme for hypertension on knowledge among elderly at the Lestari Posyandu.. This study employed a single-group pre-post pre-experimental design. The sample comprised 46 elderly, selected using purposive sampling. Data were collected via a questionnaire and subsequently analysed using the Wilcoxon test. The results of this study indicate a significant increase in knowledge levels following the intervention using the Hypertension Exercise video. Statistical analysis revealed an increase in knowledge (p-value = 0.000). The intervention using the Hypertension Exercise video was found to significantly improve the knowledge of older adults at the Lestari Posyandu.